Care Gaps and Recommendations in Vestibular Migraine: An Expert Panel Summit - Mallampalli, Monica P.; Rizk, Habib G.; Kheradmand, Amir; Beh, Shin C.; Abouzari, Mehdi; Bassett, Alaina M.; Buskirk, James; Ceriani, Claire E. J.; Crowson, Matthew G.; Djalilian, Hamid; Goebel, Joel A.; Kuhn, Jeffery J.; et al. (Frontiers in Neurology, 2022)
Vestibular migraine (VM) is an increasingly recognized pathology yet remains as an underdiagnosed cause of vestibular disorders. While current diagnostic criteria are codified in the 2012 Barany Society document and included in the third edition of the international classification of headache disorders, the pathophysiology of this disorder is still elusive. The Association for Migraine Disorders hosted a multidisciplinary, international expert workshop in October 2020 and identified seven current care gaps that the scientific community needs to resolve, including a better understanding of the range of symptoms and phenotypes of VM, the lack of a diagnostic marker, a better understanding of pathophysiologic mechanisms, as well as the lack of clear recommendations for interventions (nonpharmacologic and pharmacologic) and finally, the need for specific outcome measures that will guide clinicians as well as research into the efficacy of interventions. The expert group issued several recommendations to address those areas including establishing a global VM registry, creating an improved diagnostic algorithm using available vestibular tests as well as others that are in development, conducting appropriate trials of high quality to validate current clinically available treatment and fostering collaborative efforts to elucidate the pathophysiologic mechanisms underlying VM, specifically the role of the trigemino-vascular pathways.